2019
DOI: 10.1093/ejcts/ezz160
|View full text |Cite
|
Sign up to set email alerts
|

Isolated reoperation for tricuspid regurgitation after left-sided valve surgery: technique evolution

Abstract: OBJECTIVES This study aimed to compare the isolated replacement and repair of severe tricuspid regurgitation after left-sided valve surgery (LSVS) and to report the evolution of this surgical technique. METHODS From January 2005 to August 2018, 118 patients underwent isolated tricuspid valve replacement (iTVR, n = 93) or repair (iTVr, n = 25) for severe tricuspid regurgitation after LSVS. The surgical protocol at our institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…Another key finding was the increased mortality with higher NYHA function class. Patients with NYHA function class IV had relatively higher risk of in-hospital death with an OR of 8.525 (95% CI: 2.153-33.760,p = 0.002), and NYHA function class IV as an independent risk factor was frequently confirmed by previous studies [17,18,21,22]. Considering the high risk of higher NYHA function class, we adopted early surgery strategies and preoperative optimized medical therapy are recommended to improve heart function.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Another key finding was the increased mortality with higher NYHA function class. Patients with NYHA function class IV had relatively higher risk of in-hospital death with an OR of 8.525 (95% CI: 2.153-33.760,p = 0.002), and NYHA function class IV as an independent risk factor was frequently confirmed by previous studies [17,18,21,22]. Considering the high risk of higher NYHA function class, we adopted early surgery strategies and preoperative optimized medical therapy are recommended to improve heart function.…”
Section: Discussionsupporting
confidence: 56%
“…Early studies introduced minimally invasive tricuspid valve surgery and reported lower mortality and morbidity; our evolving surgical techniques were different from those studies [10,18]. More studies reported RITS after LSVS with a higher proportion of TVR due to leaflet structural alterations or excessive leaflet tethering in the context of a long-lasting disease when repair was difficult [10,16,18].…”
Section: Discussionmentioning
confidence: 98%
“…A total of 811 entries were obtained from the literature search, and figure 1 summarises the studies disposition. After abstract screening, 54 full-text studies were evaluated before arriving at the final 16 studies that met the inclusion criteria of this meta-analysis 6–21Table 1. lists the main characteristics of the included studies, totalling 6808 isolated tricuspid valve repairs and 8261 isolated tricuspid valve replacement patients.…”
Section: Resultsmentioning
confidence: 99%
“…In case of minimal access isolated tricuspid surgery, most of the data are collected from single centre experiences, case series and case reports (Table 1). Some relatively large volume studies showed the results of isolated tricuspid valve surgery, but they did not include subgroup comparative analysis between sternotomy and minimally invasive approaches (40). Other studies from highly experienced centres showed the results of concomitant tricuspid valve surgery during mitral valve surgery (41).…”
Section: Discussionmentioning
confidence: 99%
“…Chen and colleagues reported a total bypass time of 74.8±28.5 min in their 117 patients with isolated tricuspid surgery patients. In their series 90.7% of the patients had MITS (40). Ricci a long bypass times of 135.8±41.9 min, but their series included also concomitant procedures with the MITS (38).…”
Section: Operative Timesmentioning
confidence: 99%